Discovery and structure-activity-relationship study of novel imidazole cyclopropyl amine analogues for mutant isocitric dehydrogenase 1 (IDH1) inhibitors. Issue 23 (15th December 2018) - Zheng, Qiangang; Chen, Ziqi; Wan, Huixin; Tang, Shuai; Ye, Yan; Xu, Yuan; Jiang, Lei; Ding, Jian; Geng, Meiyu; Huang, Min; Huang, Ying
Graphical abstract: Highlights: Synthesis of novel mIDH1 inhibitors with novel imidazole cyclopropyl amine analogues via three steps reaction. Structure based rational drug design guided by CADD and microsome stability improvement guided by metID. 5t shows potent enzymatic and cellular activities, moderate liver microsome stability and PK properties. 5t might be a lead compound deserved further structural optimization. Abstract: The discovery and optimization of imidazole cyclopropyl amime analogues as mutant IDH1 inhibitors via structure-based rational design were reported. The optimal compounds demonstrated both potent inhibition in IDH1 R132H enzymatic activity and 2HG production in IDH1 mutant HT1080 cell line, moderate liver microsome stability and PK properties.